Retrospective Matched-Pair Cohort Study on Effect of Bisegmental Fenestration versus Hemilaminectomy for Bisegmental Spinal Canal Stenosis at L3–L4 and L4–L5 - Schüppel, Julia; Weber, Friedrich (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background The main symptoms of degenerative lumbar spinal canal stenosis are progressive back pain, spinal claudication, and, occasionally, sensory and motor deficits. Impairments particularly occur during walking, standing, and sitting. Thus social and vocational activities are increasingly restricted, causing considerable suffering for patients. Surgical therapies are superior to conservative ones. This article studies the outcome of 2-level fenestration versus hemilaminectomy for bisegmental spinal stenosis decompression.Methods This retrospective matched-pair cohort study included a total of 144 patients who underwent surgery for bisegmental spinal stenosis at the levels L3-4 and L4-5 between 2008 and 2012. There were 72 matching pairs that corresponded in sex, year of birth, and width of the stenosed segments. The patients' impairments were reported before, immediately after, and 6 and 12 months after surgery using the Oswestry Disability Questionnaire (ODQ-D) and the EuroQol-5D (EQ-5D). The data were evaluated statistically.Results The comparison of both surgical procedures regarding walking ability (walking a distance with and without a walking aid) revealed a significant difference. Patients who underwent hemilaminectomy had better postoperative results. The individual criteria of the ODQ-D and EQ-5D revealed no significant differences between 2-level fenestration and hemilaminectomy; however, there is always significant postoperative improvement in comparison with preoperative status. Age, sex, body mass index, comorbidities, smoking, and alcohol consumption had no influence on the surgical results. The reoperation rate was between 13% and 15% for both surgical techniques, not being significantly different.Conclusion Fenestration and hemilaminectomy are equivalent therapies for bisegmental lumbar spinal canal stenosis. Regarding walking, the study revealed better results for hemilaminectomy than for fenestration in this cohort of patients. Pain intensity, personal care, lifting and carrying of objects, sitting, social life, and travel all improved significantly postoperatively as compared with preoperatively. In both groups, health status as the decisive predictor improved considerably after surgery. We could show that both surgical methods result in significant postoperative improvement of all the individual criteria of the ODQ-D and the EQ-5D.
Keywords: spinal stenosis; fenestration; hemilaminectomy